2021
DOI: 10.1002/bse.2854
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy in corporate sustainability reporting: A review of organisational approaches

Abstract: A growing commitment from companies to implement circular economy (CE) strategies demands the development of guidelines for consistent related external communication. The fields of non-financial reporting and sustainability are well established with numerous available international reporting frameworks and approaches; however, there is still an absence of standardised reporting principles and procedures for publishing progress on circularity. In this context, this article aims to explore how companies could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 121 publications
0
42
0
Order By: Relevance
“…However, we have found that companies obtained numerous benefits through the process of developing tailor‐made CE assessment approaches, benefits which would be potentially reduced, if standardisation was to occur in an overly prescriptive way. At the same time, it is important to acknowledge that companies selecting their own CE indicators opens the doors for incidences of greenwashing, as observed in recent studies on CE assessment and reporting guidelines (Opferkuch et al, 2021; Pauliuk, 2018). These studies indicated that companies are able to cherry‐pick CE indicators, reporting more on aims and intentions, rather than actual performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have found that companies obtained numerous benefits through the process of developing tailor‐made CE assessment approaches, benefits which would be potentially reduced, if standardisation was to occur in an overly prescriptive way. At the same time, it is important to acknowledge that companies selecting their own CE indicators opens the doors for incidences of greenwashing, as observed in recent studies on CE assessment and reporting guidelines (Opferkuch et al, 2021; Pauliuk, 2018). These studies indicated that companies are able to cherry‐pick CE indicators, reporting more on aims and intentions, rather than actual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Since sustainability assessment is a field with a longer history, more information on its degree of implementation by companies is available. In fact, sustainability tools, initiatives and approaches, such as corporate social responsibility (CSR) and the GRI, are well known among companies (Lozano, 2020); however, their uptake of CE issues is lacking and less concrete (Opferkuch et al, 2021).…”
Section: Ce and Sustainability Assessment Approaches For Companiesmentioning
confidence: 99%
“…According to Opferkuch et al (2021), corporate sustainability reporting could address these barriers and allow stakeholders to make reliable evaluations of non-financial performance, including the social and environmental aspects of businesses within a circular economy. The authors draw attention to other benefits, including credibility, reduced legal risks, improved supplier relationships, increased access to capital and ethical behaviour along the supply chain [7]. However, the authors also highlight the need for guiding principles and procedures before corporate sustainability reporting can be introduced.…”
Section: The Argument For Design Circularity As a Template For Circul...mentioning
confidence: 99%
“…Amini et al (2018) used content analysis to investigate non-financial reports and map corporate sustainability definitions and frameworks. More recently, Opferkuch et al (2020) analysed circular economy approaches and business models by a sample of international companies, building on the data and information contained in their sustainability reporting.…”
Section: Assessmentmentioning
confidence: 99%